Konseling Lintas Budaya: Sebagai Upaya Preventif Pernikahan Dini - Rahmaditta Kurniawati; Nurus Sa’adah (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to describe the role of cross-cultural counseling as a preventive effort in cases of early marriage. The method used in this study is a qualitative method, with the type of literature study or literature review. Researchers collected various books and articles related to the topic of discussion and then analyzed them. Based on the results of the analysis of the literature review, there are various factors behind early marriage including: 1) education, 2) culture, 3) environment. The findings also reveal that there are two techniques of cross-cultural counseling as an effort to prevent early marriage, including: first, counseling conducts discussions and collaborations in every line of the community sector. Second, the counseling session is accompanied by a counselor with cultural sensitivity competence as a catalyst. Counselors are tasked with educating the public or clients about the importance of preparing for marriage and the impact of early marriage. So cross-cultural counseling as an effort to prevent early marriage is a tool owned by counselors, namely through a cultural approach